The Effect of Competence, Time Budget Pressure and Professional Attitudes of Auditors on Internal Audit Quality With Role Conflict As a Moderating Variable - Nurmawanti, Sylvia; Lenggogeni, Lenggogeni; Yanti, Harti Budi (Dinasti Publisher, 2024)
This study aims to analyze the effect of competence, time budget pressure and professional attitudes of Inspectorate auditors on audit quality with role conflict as a moderating variable. The population in this study were all functional auditors who worked in the Banten Province Regional Inspectorate which consisted of 62 auditors. The sampling technique in this study was to use the census method. This technique was chosen because the researcher has a consideration that the total number of auditors at the Inspectorate of Banten Province is still relatively small and can be used as a sample entirely. The data analysis method uses descriptive analysis and multiple linear regression. Based on the results of this study indicate that competence, time budget pressure and professional attitudes of auditors have a positive effect on audit quality. In addition, role conflict is unable to moderate the relationship between competence, time budget pressure and professional attitudes of auditors with audit quality